Manajemen Nyeri Persalinan Dengan Peanut Ball Sebagai Upaya Peningkatan Kesiapan Menghadapi Persalinan pada Ibu Hamil Trimester 3 di Wonokromo - Fritria Dwi Anggraini; Nur Zuwariyah; Nur Masruroh; Farida Umamah; Fariska Zata Amani; Machmudah Machmudah (Jurnal Pepadu, 2026)
Childbirth should ideally be welcomed with positive emotions such as enthusiasm, comfort, and a strong sense of readiness (Wijma, 2017). However, in reality, psychological issues commonly arise, particularly anxiety before labor, which often leads mothers to feel unprepared for childbirth. This anxiety stems from concerns about the baby’s condition and fear of being unable to cope with the pain caused by uterine contractions. As a result, mothers may feel unsure and lack confidence in their ability to undergo labor safely and comfortably, causing them to feel unready as they approach term. This community engagement program aims to address these needs through a preventive approach, specifically by enhancing childbirth readiness and strengthening pain management skills among third-trimester pregnant women. The intervention introduces non-pharmacological pain management using the Peanut Ball as a practical method to support mothers during late pregnancy. The target participants were pregnant women residing in the catchment area of Wonokromo Public Health Center, particularly those in RW 01 and RW 04, along with local health cadres. Education was provided through one-on-one home visits involving explanation, hands-on demonstration, and guided practice using prepared educational materials, including leaflets and the Peanut Ball. The program outcomes showed an improvement in both physical and psychological readiness for childbirth, measured using the Childbirth Readiness Scale (CRS), increasing from 65% to 82.1%. This program proved effective in enhancing childbirth preparedness and can be adopted as a community-level non-pharmacological intervention. Through this intervention, mothers are expected to better manage contraction-related pain and approach labor with improved physical and psychological readiness.